Análise estratégica da advocacia empresarial a partir da visão baseada em recursos - Breyer, Thiago Beiler dos Santos (Universidade do Vale do Rio dos Sinos, 2015)
Business transformations experienced by businesses in recent years reached the legal world. And several authors in articles and publications refer to the legal market in transformation, particularly in relation to the field of Business and Corporate Law. Among the many reasons for this transformation on Business and Corporate Law, it can be presented the changes in management and strategic positioning due to market factors, such as technology, economic, financial partner and the effects of globalization itself. It is observed, however, that even though business organizations have evolved and improved administrative and strategically, the same can not be said of business and corporate law, taking in account that for many years it remained inert in its strategy, management and administrative organization. It happens that after a certain time, the companies that, by necessity, interest in growth or competitiveness came to professionalize themselves, and began to demand the same of its suppliers, including the Corporate Law Firms. For all this and the growing numbers of lawyers and corporate business lawyers, it is necessary to business law professionals a clear and timely strategy, geared and focused to the characteristics of their industry, namely, the provision of services taking knowledge as essential element of its performance. The Resource Based View ('VBR') meets this strategic need of business law, to force its strategy on internal resources of a business organization as an element and guidance strategy of its theory, meeting the wishes and needs of law business. This study analyzes the business advocacy strategy based on the concepts and VBR resources as a central strategic guidance starting from the this guidance coming from the field of literature, People, Technology, Organization, price and geography that aligned with the concepts and strategic resources of VBR as a central reference to outline the strategic direction of a business law firm
Keywords: Mercado jurídico; Advocacia empresarial; Estratégia; Estratégia jurídica; Visão baseada em recursos (“VBR”); Pessoas; Tecnologia; Organização; Preço; Geografia; Legal market; Business law; Corporate law; Strategy; Legal strategy; Resource-based view (‘RBV’); People; Tecnology; Organization; Price; Geography; ACCNPQ::Ciências Sociais Aplicadas::Administração